FAKTOR FAKTOR YANG MEMPENGARUHI PENDAPATAN DAN STRATEGI PENGEMBANGAN BUDIDAYA IKAN MAS KOKI DI DESA WAJAK LOR KECAMATAN BOYOLANGU KABUPATEN TULUNGAGUNG - mukhamad fakhrur roziq; Soetriono Soetriono; Anik Suwandari (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
Based on the data from Department of Fisheries Tulungagung shows that the production of fancy goldfish at Tulungagung in 2014 (to the third quarter) has decreased up. This study aims to determine: (1) the management of fancy goldfish breeding (2)What are the factors that affect the revenue (3) business development strategies of fancy goldfish breeding? The determination of the research at Wajak Lor village, Boyolangu, Tulungagung. The method used is descriptive analysis method. The sampling method, it was done by taking the sample using simple random sampling and purposive sampling. This research used primary and secondary data. Methods of data analysis used descriptive analysis, multiple regression and force field analysis. The results showed: (1) the management of the fancy goldfish breeding by experience , (2) cost of the feed and the seed that negatively affect the revenue, on the contrary, the volume of the pond, production and the selling price positively affect, the labor costs do not significantly affect, (3) business development strategies of fancy goldfish breeding by improving the product quality of fancy goldfish breeding, and by cooperating with the government to know the weather predictions in the future and about good breeding from Department of Fisheries Tulungagung.